Utilization of LDR Sensor on Light Follower Robot with Holonomic Concept as Learning Media - Harlan Kurnia AR (Journal of Computer Science and Informatics Engineering, 2024)
Learning media is always evolving from time to time. At this time, learning media can use robotics by utilizing the LDR sensor on the Light Follower Robot with the Holonomic Concept. The use of conventional methods in the construction of wheeled robots has begun to be abandoned because of its limited movement. Currently the world of robotics already uses sensors, one of which is the LDR sensor which is the most common light sensor to know. Because in addition to the affordable price, this sensor has also been widely used in everyday life. By using sensors that are well known to many people, this research also aims to open up insights that sensors that are considered normal can also be used in the manufacture of robots. The way it works will start from assembling the Laser Pointer and LDR sensor then sending the reading results to the ATMega8535 microcontroller and forwarding it to the program module, with the output in the form of characters to the LCD.